EVALUASI PELATIHAN GURU DI SMP NEGERI 3 HILISERANGKAI KABUPATEN NIAS - Waruwu, Niska Walfiatni; Ndraha, Ayler Beniah; Waruwu, Meiman; Telaumbanua, Eliagus (FEB Universitas Sam Ratulangi Manado, 2023)
This research aims to: 1) To find out the role performed by the Village Head in managing institutional cooperation in the Tetehosi I village government of Gunungsitoli City. 2) To find out the supporting and inhibiting factors of the village head in managing institutional cooperation in the Tetehosi I village government of Gunungsitoli City. 3) The author determines that this research is carried out in a qualitative type of research with a descriptive approach because this type of research has the aim of describing and analyzing phenomena, events, or social activities that occur in society that occur in the present in Tetehosi I village. The results of this study are: 1) the role of the village head is very relevant to the objectives of institutional cooperation in Tetehosi I Village. 2) a. Supporting factors: Active in carrying out tasks, Strong communication, Support and motivation, Controlling the decision-making process, Inclusiveness in decision-making, Encouraging active involvement of team members. b. Inhibiting factors: Limited Information Dissemination, Lack of active involvement of team members, Differences in Priorities and Focus, Lack of Community Participation. 3) The Tetehosi I Village Head has implemented several important strategies to manage institutional cooperation. In addition, the Tetehosi I Village Head should prioritize improving communication and active involvement in managing institutional cooperation in the Tetehosi I Village government, the Village Head should improve the existing supporting components, also remain active in carrying out tasks and ensure strong communication with all communities and institutions.